2012
DOI: 10.1002/ejoc.201101831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Structure, and Properties of 2‐(2‐Hydroxyphenyl)‐1‐azaazulene

Abstract: We herein report the synthesis of 2‐(2‐methoxyphenyl)‐1‐azaazulene (8) by a Suzuki–Miyaura cross‐coupling reaction between 2‐chloro‐1‐azaazulene and 2‐methoxyphenylboronic acid and also by the condensation of tropone and the ylide derived from 1‐(o‐methoxyphenacyl)pyridinium iodide. Demethylation of 8 afforded the title compound 6. X‐ray crystallographic analysis of 6 provided evidence for an intramolecular hydrogen bond between the phenolic hydrogen atom and the nitrogen atom of the azaazulenyl ring and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…1-Azaazulene with a phenol functional group at the 2-position has been synthesized by Oda et al 26 This structure is similar to 8-hydroxyquinoline, which is an important chelating agent. 27 , 28 Thus, 2-(2-hydroxyphenyl)-1-azaazulene ( 2OHPhAZ ) has the potential to be used as a chelating ligand through the imino nitrogen atom and the phenolic oxygen atom.…”
Section: Introductionmentioning
confidence: 99%
“…1-Azaazulene with a phenol functional group at the 2-position has been synthesized by Oda et al 26 This structure is similar to 8-hydroxyquinoline, which is an important chelating agent. 27 , 28 Thus, 2-(2-hydroxyphenyl)-1-azaazulene ( 2OHPhAZ ) has the potential to be used as a chelating ligand through the imino nitrogen atom and the phenolic oxygen atom.…”
Section: Introductionmentioning
confidence: 99%
“…The combined organic layers were washed with brine (5 mL), and dried over anhydrous MgSO4. Filtration was concentrated in vacuo, and the residue was purified by column chromatography (silica gel, 90% EtOAc in hexane) to provide 14 (11…”
Section: -Phenylcyclohepta[b]pyrrol-4(1h)-one (14)mentioning
confidence: 99%
“…1 Of the many azaazulenes, 1-azaazulenes have attracted considerable attention from chemists because of their stabilities and pharmacological activities. [2][3][4] While many examples of 1-azaazulene syntheses have been reported, [5][6][7][8][9][10][11] in most cases, troponoid compounds were used as starting materials. For example, Nitta and co-workers successfully synthesized various 1-azaazulene derivatives 3 from tropones 1 using the aza-Wittig reaction followed by the oxidation of the bicyclic intermediates 2 (Scheme 1, A).…”
mentioning
confidence: 99%
“…Slight difference between two spectra may be attributed to its conformational change by hydrogen bond in the protic solvent, as seen in 1. [12] a) 7 (X=I) was added to the reaction mixture in portions during a time of 6 hr. b) 7 (X=I) was added to the reaction mixture in portions during a time of 9 hr.…”
Section: Scheme 1 Synthesis Ofmentioning
confidence: 99%
“…1, and studied ability of 1-azaazulenes [6][7][8][9] as a ligand for metal ions and as a base for Brønsted acids. [10][11][12] It was found that 2-(pyrid-2-yl)-1-azaazulene (1) chelated with metal ions and bound with proton and, then, showed the enhanced emission upon photoexcitation. [10] During a course of our study, we have been interested in a pincer ligand having 1-azaazulenyl groups.…”
Section: Introductionmentioning
confidence: 99%